Sclerotium rolfsii, Penyebab Penyakit Busuk Pangkal Batang pada Hippeastrum sp. - Antok Wahyu Sektiono; Syamsuddin Djauhari; Putri Devinta Pertiwi (Jurnal Fitopatologi Indonesia, 2019)
Sclerotium rolfsii, a the Causal Agent of Stem Rot Disease on Hippeastrum sp.Symptoms of stem rot that cause Hippeastrum sp. or red lily wither, leaves turn yellow, and eventually die found at Mangliawan Village, District of Pakis, Malang - East Java. The purpose of this study was to identify the pathogens that cause root rot disease on lily plants and find out their host range. Sclerotium from the symptomatic base of the plant was isolated on potato dextrose agar medium. Fungus was identified based on the morphological characteristics of the colonies and mycelium. Host range test of pathogen was carried out by manual inoculation on Rain lily (Zephyranthes) St. Bernard's lily (Chlorophytum) and Beach Spider lily (Hymenocallis). The results of the identification showed that the fungus had white mycelium and formed sclerotium. Sclerotium is irregularly rounded, white when young, and dark brown when ripe, and forms 10 days after incubation. In hyphae, there are branching, septa, and clam connections. Based on the morphological characteristics of the disease the fungus was identified as Sclerotium rolfsii. In the host range test, the fungus was able to infect rain lilies and paris lilies, but not in spider lilies. This is the first report of S. rolfsii infection in lily in Indonesia.